Gereja Sebagai Shelter: Gerakan Shelter COVID-19 sebagai Model Katekese untuk Solidaritas di Masa Pandemi - Alexander Hendra Dwi Asmara (Asosiasi Teolog Indonesia, 2022)
As the Catholic Church’s response to the COVID-19 crisis in Indonesia has changed over time, Yogyakarta—which is under the Archdiocese of Semarang (Keuskupan Agung Semarang, or KAS)—has seen a significant shift in the Church’s approach. During the first pandemic phase (2020), the KAS was more focused on offering short-term assistance, such as distributing face masks, providing food or meals, and organizing other charitable activities. But by the second period of the COVID-19 pandemic (2021), the KAS shifted to more comprehensive approaches, specifically the opening of self-isolation shelters for COVID-19 patients. This article demonstrates how providing shelter has become a new model for the Church to symbolize its deep solidarity with the afflicted in a time of pandemic. The qualitative data collection methods employed include interviews with several key informants, with details corroborated by information from the internet and other mass media.